Grid interface control of wind–solar generator in Hail region of Saudi Arabia using FOPI controller - Younsi, Sami; Kahouli, Omar; Alsaif, Haitham; Ali, Naim Ben; Chaabane, Mohamed (Frontiers in Energy Research, 2023)
This study investigates the performance of a wind–solar generator (WSG) in the Hail region of Kingdom of Saudi Arabia (KSA) with a fractional order PI controller (FOPI) applied to the grid connection line. The proposed hybrid generator consists of a wind turbine with a PMSM machine and a PV panel connected to a secondary distribution grid by a DC link, three-phase inverter, and an RL filter. The line currents injected into the grid and/or loads are controlled by calculating the output reference voltage of an inverter and by the reference active and reactive requested powers. For this purpose, control loops around the RL filter were developed with fractional-order proportional-integral (FOPI) controllers, and a comparison with classic PI controllers was made. The system was simulated using the MATLAB/Simulink software. The results showed that the generator satisfied the power demand under the climatic conditions of the Hail region. They also demonstrated the good performance of the proposed controllers, which had good tracking accuracy and robustness to variations in wind speed and power demanded by loads in a very short time. The FOPI controller exhibited faster dynamic response and less overshoot than the classic PI controller.